2020
DOI: 10.5194/amt-2019-494-ac2
|View full text |Cite
|
Sign up to set email alerts
|

Response to the reviewer 1 of the manuscript: “Comparison of different droplet measurement techniques in the Braunschweig Icing Wind Tunnel” by Inken Knop et al.

Abstract: Interactive comment on "Comparison of different droplet measurement techniques in the Braunschweig Icing Wind Tunnel" by Inken Knop et al. Inken Knop et al.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…This leaves us with the smallest group of SLSNe, which Gal-Yam (2012) defined as SLSN-R, for radioactive. This group includes only a small number of SNe, notably SN 2007bi, SN 1999as, the first SLSN observed (Knop et al 1999), PTF12dam (Nicholl et al 2013), SN 2015bn (Jerkstrand et al 2016;Nicholl et al 2015), and PS1-14bj (Lunnan et al 2016). While also showing SN Ic spectra, these SNe decline slowly in luminosity, following the 56 Co decline rate, and are not known to show O II lines early on (but early observations are scarce and the rise time is highly uncertain).…”
Section: Introductionmentioning
confidence: 99%
“…This leaves us with the smallest group of SLSNe, which Gal-Yam (2012) defined as SLSN-R, for radioactive. This group includes only a small number of SNe, notably SN 2007bi, SN 1999as, the first SLSN observed (Knop et al 1999), PTF12dam (Nicholl et al 2013), SN 2015bn (Jerkstrand et al 2016;Nicholl et al 2015), and PS1-14bj (Lunnan et al 2016). While also showing SN Ic spectra, these SNe decline slowly in luminosity, following the 56 Co decline rate, and are not known to show O II lines early on (but early observations are scarce and the rise time is highly uncertain).…”
Section: Introductionmentioning
confidence: 99%
“…Remarkably, CATS results include observations of SN 2002ic, the first SN Ia showing interaction with a dense circumstellar medium (Hamuy et al 2003), and SN 2003bg the first Type IIb hypernova (Hamuy et al 2009). Here we add to these notable achievements, the observations of SN 2002gh, the second SLSN discovered after SN 1999as (Knop et al 1999), for which its superluminous nature remained unnoticed for nearly two decades until now. In Section 2, we describe the data reduction and present the observations.…”
Section: Introductionmentioning
confidence: 87%
“…Objects such as SN 1999as (Knop et al 1999), SN 2005ap (Quimby et al 2007), SCP 06F6 (Barbary et al 2009), and SN 2007bi (Gal-Yam et al 2009 were the first SLSN-I reported, several years before they were distinguished as a separate SN class. Their bright peak luminosities together with the identification of a common set of spectral features made it possible to distinguish them as members of a completely new SN class (Quimby et al 2011).…”
Section: Introductionmentioning
confidence: 99%